Cognitive therapy - Beck, Judith S.; Carlson, Jon (APA psychotherapy series, 2006)
In Cognitive-Behavior Therapy. Jacqueline B. Persons demonstrates this frequently used system of psychotherapy. Dr. Persons uses a case conceptualization as a guide for choosing